2022
DOI: 10.1016/j.ijid.2021.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Surging bloodstream infections and antimicrobial resistance during the first wave of COVID–19: a study in a large multihospital institution in the Paris region

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…Notwithstanding the heterogeneity of study designs, for the most part, the evidence suggests that there was a dramatic surge of BSIs, HOIs, central line associated blood stream infections (CLABSIs) and episodes of ventilator-associated pneumonia (VAP) caused by GNB, during the pandemic globally. These significant variations were generally most evident in large, system-wide regional or national hospital and surveillance networks [11 ▪ –14 ▪ ,15,16 ▪ ], and coinciding with this, was a substantial increase in one or more of the major GNB pathogens, that is K. pneumonia e (K. pneumoniae) [11 ▪ ,14 ▪ ,16 ▪ ], P. aeruginosa [11 ▪ ,14 ▪ ,16 ▪ ,17] and A. baumannii [12 ▪ ,18].…”
Section: Variation In Epidemiology Of Gram-negative Infections Before...mentioning
confidence: 88%
See 2 more Smart Citations
“…Notwithstanding the heterogeneity of study designs, for the most part, the evidence suggests that there was a dramatic surge of BSIs, HOIs, central line associated blood stream infections (CLABSIs) and episodes of ventilator-associated pneumonia (VAP) caused by GNB, during the pandemic globally. These significant variations were generally most evident in large, system-wide regional or national hospital and surveillance networks [11 ▪ –14 ▪ ,15,16 ▪ ], and coinciding with this, was a substantial increase in one or more of the major GNB pathogens, that is K. pneumonia e (K. pneumoniae) [11 ▪ ,14 ▪ ,16 ▪ ], P. aeruginosa [11 ▪ ,14 ▪ ,16 ▪ ,17] and A. baumannii [12 ▪ ,18].…”
Section: Variation In Epidemiology Of Gram-negative Infections Before...mentioning
confidence: 88%
“…In a multicentre 25-hospital network in France, Amarsy et al [11 ▪ ] found that the rate ratio of BSIs per 100 admissions increased by 24% and 115% in March 2020 and April 2020, respectively compared to prepandemic rates, and coincided with an increase in the major GNB pathogens. In another large study, from Brazil involving ICU patients across 99 hospitals, de Carvalho Hessel Dias et al [12 ▪ ] reported increases in the incidence of both VAP and CLABSI and a significant increase in the incidence density of A. baumannii .…”
Section: Variation In Epidemiology Of Gram-negative Infections Before...mentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of poor case ascertainment and notification could be raised to explain the decreases while countries were responding to the surge of COVID-19. However, we studied S. pneumoniae and S. pyogenes invasive infections diagnosed in the hospital setting, where an increase in the number of blood cultures collected, in particular during the first wave has been reported 12 . Hence, the reductions by 34% for S. pneumoniae and 28% for S. pyogenes observed in 2020 in our facilities are likely to be consistent with actual decreases in incidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies could also use prospective data or data linkage that can offer important paths for future evidence. Some studies using these methods found that BSI as a whole increased in the pandemic, contamination rates increased with ICU bed surges, and any BSI increased mortality [ 18 , 22 , 43 ]. A large collection of patient data using these study methods could construct a laboratory algorithm model, similar to prediction models created for severe COVID-19 or mortality, to better predict bacterial coinfection in patients and ensure they are appropriately treated [ 44 48 ].…”
Section: Discussionmentioning
confidence: 99%